Comments on fire! Classifying flaming comments on YouTube videos in Malaysia - Revathy Amadera Lingam; Norizah Aripin (Penerbit Universiti Kebangsaan Malaysia, 2017)
Flaming refers to the use of offensive language such as swearing, insulting and providing hateful comments through an online medium. In this study, the act of flaming will be explored in the context of social media, particularly YouTube. The research aims to discover the types of comments that are found on Malaysian themed YouTube videos and classify them accordingly. The Uses and Gratification theory was used as a base to explain the satisfaction obtained through YouTube as a platform to express via comments; hence obtain satisfaction through negativity. The methodology employed to carry out the study was through a content analysis. One video from the top 5 YouTube category namely entertainment, film and animation, news and politics, comedy and people and blogs were chosen with at least 100,000 views and a minimum of 100 comments. Top 100 flames were then sorted out for each video and analyzed using the thematic analysis approach. The results of this study show that the two most frequent types of comments found on Malaysian videos are political attack and racial attack. Other subcategories that are also driving the two categories mentioned above are stereotypes, speculation, comparison, degrading comments, slander/defame, sedition, sarcasm, threaten, challenge, criticism, name-calling, and sexual harassments. Through this study, the severity of the issue of flaming on account of YouTube comments has been identified; enabling the concerning party to take proper action including the use of artificial intelligence against cyber-bullying.